Pengembangan Media Etnomatematika Berbasis Augmented Reality (EMAR) Untuk Penguatan Penalaran Spasial Siswa di Sekolah Dasar - Fathuloh, Ridwan; Sutama, Sutama; Kholid, Muhammad Noor; Minsih, Minsih (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to (1) develop EMAR (Augmented Reality-Based Ethnomathematics) media and (2) determine the feasibility of EMAR media related to building materials for cube and block spaces through validity, practicality, and effectiveness tests. The method used is research and development (R&D) with the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques include observation, interviews, and validation questionnaires. The results of the analysis show that students have difficulties in understanding the materials of building spaces, so more creative learning media is needed. The product developed is an EMAR application which contains materials that are characteristic and volume of building space. The validation results by material experts reached 85.5% and by media experts 92.2%, both in the very feasible category. In addition, the results of the independent t-test showed a significant difference between the post-test scores of students who used EMAR media and those who did not, with a significance value of 0.033, indicating that this media was effective in improving students' spatial reasoning. This research is expected to increase students' understanding of space building materials in a fun and relevant way.